SMAD4 Somatic Mutations in Head and Neck Carcinoma Are Associated With Tumor Progression - Lin, Li-Han; Chang, Kuo-Wei; Cheng, Hui-Wen; Liu, Chung-Ji (Frontiers in Oncology, 2019)
As the incidence and the mortality rate of head and neck squamous cell carcinoma (HNSCC) is increasing worldwide, gaining knowledge about the genomic changes which happen in the carcinogenesis of HNSCC is essential for the diagnosis and therapy of the disease. SMAD4 (DPC4) is a tumor suppressor gene. It is located at chromosome 18q21.1 and a member of the SMAD family. Which mediates the TGF-β signaling pathway, thereby controlling the growth of epithelial cells. In the study presented here, we analyzed tumor samples by multiplex PCR-based next-generation sequencing (NGS) and found deleterious mutations of SMAD4 in 4.1% of the tumors. Knock-down experiments of endogenous and exogenous SMAD4 expression demonstrated that SMAD4 is involved in the migration and invasion of HNSCC cells. Functional analysis of a missense mutation in the MH1 domain of SMAD4 may be responsible for the loss of function in suppressing tumor progression. Missense SMAD4 mutations, therefore, could be useful prognostic determinants for patients affected by HNSCCs. This report is the first study where NGS analysis based on multiplex-PCR is used to demonstrate the imminent occurrence of missense SMAD4 mutations in HNSCC cells. The gene analysis that we performed may support the identification of SMAD4 mutations as a diagnostic marker or even as a potential therapeutic target in head and neck cancer. Moreover, the analytic strategy proposed for the detection of mutations in the SMAD4 gene may be validated as a platform to assist mutation screening.